PENGARUH OPINI AUDIT TERHADAP GOOD PUBLIC GOVERNANCE DALAM MENJAMIN KELANGSUNGAN HIDUP PERUSAHAAN - Ratih Andaningsih (Jurnal Manajemen FE-UB, 2017)
The objective of this research is to examine of influence audit opinion to good public governance in secured of going concern of the corporation. The Conception of national good public governance  policy , through the recommendation  of  the  board  of  the National Good Public Governance of Indonesia,placing public service as one elements that must be undertaken by the state.The process of e governance of sustainability development to be good going concern, and facilities in order to meet the needs of man power in the research and development financial institution,and insurance industry. The purpose of this research is how the strategy to the needs of space education and awareness taking into account its interest,perceptions and strategic environment and public policy. Descriptive method qualitative and quantitative analysis by conducting comparative implementation in Indonesia. Survey with indept interviews of relevant stakeholders conducted representing and research development institutions about good public governance policy perceptions.The companies have get of the auditor’s going concern opinion  was  caused  of conditions and events that give rise to doubts about the viability of a company. Going concern audit opinion is an early warning for the users of the financial statements in order to avoid decisions making errors. Going concern audit opinion can be insured to give opinion’s auditor in credibility of life insurance business.The Sampling technic in this research was purposive sampling, there life insurance companies in Indonesia.The Data analysis technique used regresi logistic and hyphotesis 0,05 in this study is multiple regression analysis. Based on the results of this study indicate that opinion have positive and significant impact on going concern audit opinion. While there is no positif and significant impact on going concern audit opinion. Keywords: audit opinion,Governance, Going concern